Estudios de actividad antioxidante en fracciones provenientes de dos plantas medicinales ecuatorianas: extractos hidroalcohólicos de mashua (Tropaeolum tuberosum (Ruíz Y Pavón) tropaeolacea) y aceite esencial de congona (Peperomia inaequalifolia (Ruíz Y Pavón) Piperaceae). - Aillón Rojas, Cristina Lorena (2014)
They investigated two medicinal plants native to the Ecuadorian highlands, these plants are congona Peperomia inaequalifolia. Piperaceae (Ruíz & Pavón) and Mashua Tropaeolum tuberosum.tropaeolaceae (Ruíz & Pavón). The essential oil obtained from the species hidrodestilation Peperomia inaequalifolia (Congona) antioxidant activity resulted IC50 DPPH of 2.22 mg/mL e IC50 ABTS of 0.006mg/mL compared with Thymus vulgaris (tomillo) like positive control. During the study investigated taxonomic and ethnobotanical features and obtained representative samples of the two plants, with them essential oil of congona is extracted in the foundation CHANKUAP, in Macas city, whose fresh plant performance was 0.1607%. This oil was characterized by its chemical composition, by gas chromatography coupled to mass (CG-MS) which showed that the oil has Safrole, Myristicin, and stearil- palmitate within the most abundant compounds. Were tested for antioxidant activity as DPPH and ABTS test whose values of Ic50 were 2.157 mg/mL and 0.1860mg/mL respectively. Also underwent thin layer chromatography which confirmed the antioxidant activity of the oil to be a bleaching reagent of DPPH from violet to yellow. As for the dry extract of Tropaeolum tuberosum (Mashua) obtained by percolation antioxidant activity resulted IC50 DPPH of 0.788mg/mL e IC50 ABTS of 0.09mg/mL compared with Camellia sinensis and ascorbic acid like positive control. In addition quantitation of phenolic compounds by the method of Folin-Colicialteu and total flavonoids by the method of aluminum chloride in which results showed that the dry extract of Tropaeolum tuberosum no significant amounts of flavonoids and phenolic compounds.